MAIN DIRECTIONS OF BANK LOANS IN CREDIT MARKET - EYVAZLI, Huseyn Mubariz (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Financial analysis in credit market and commercial banks, which have been an important factor of economy and human life and activity currently, study of financial-economic results of activity of a bank, determination of main directions of development of the bank and main factors of financial business processes, determination of purpose-oriented special knowledge and growth rates, etc. Different economic sources, internet materials have been applied as a theoretical and methodological basis. As systematization of loans in bank lending system is a theme of the research, methods such as analysis, induction and deduction have been used. Main scientific innovation that has been put forward: In this field, one of the most important issues is, certainly, organization of organization system of information issues, which have the most significant role in determining and implementation of successful demand and supply of bank loans in credit market and main directions of bank loans in credit market. Results of the research: Finding perspective improvement ways of commercial banks Development of credit system, directly improved by banks, significantly positively effects progress of country economy Information tools and technology play the most important role in improving credit market now.